Synthesis and Antiproliferative Properties of Bifunctional Allocolchicine Derivatives - Gracheva, Iuliia A.; Svirshchevskaya, Elena V.; Faerman, Vladimir I.; Beletskaya, Irina P.; Fedorov, Alexey Yu. (Synthesis, 2018)
Based on the natural antimitotic agent colchifoline as a lead structure, a series of novel bifunctional allocolchicine congeners were synthesized from commercial colchicine. The new derivatives maintain good cytotoxicity against T3M4, MiaPaCa-2, and PANC-1 cell lines. The presence of functional groups simplifies further modifications of the prepared structures and the design of novel colchicine-derived antitumor compounds with desired pharmacological properties.
Keywords: antitumor agents; colchicine; allocolchicine; tubulin; bifunctional derivatives